Immunotherapeutic Potential of Extracellular Vesicles - Zhang, Bin; Yin, Yijun; Lai, Ruenn Chai; Lim, Sai Kiang (Frontiers in Immunology, 2014)
Extracellular vesicles or EVs is a term that encompasses all classes of secreted lipid membrane vesicles. Despite being scientific novelties, EVs are gaining importance as a mediator of important physiological and pathological intercellular activities possibly through the transfer of their cargo of protein and RNA between cells. In particular, exosomes the currently best characterized EVs have been notable for their in vitro and in vivo immunomodulatory activities. Exosomes are nanometer-sized endosome-derived vesicles secreted by many cell types and their immunomodulatory potential is independent of their cell source. Besides immune cells such as dendritic cells, macrophages and T cells, cancer and stem cells also secrete immunologically active exosomes that could influence both physiological and pathological processes. The immunological activities of exosomes affect both innate and adaptive immunity and include antigen presentation, T cell activation, T cell polarisation to Tregs, immune suppression and anti-inflammation. As such, exosomes carry much immunotherapeutic potential as a therapeutic agent and a therapeutic target.